Henge’dho Seni Mengungkapkan Isi Hati - Bangngu, Harini Edgina Mariana; Pudjibudojo, Jatie K (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2019)
Sabu adalah sebuah pulau yang terletak di Propinsi Nusa Tenggara Timur. Masyarakat ini memiliki sebuah tradisi unik dalam menjalin dan mempertahankan hubungan antar sesama tanpa memandang jenis kelamin, suku, ras, agama, status, usia serta strata sosial yang disebutÃ‚Â hengeÃ¢â‚¬â„¢dho (cium hidung). HengeÃ¢â‚¬â„¢dho merupakan bentuk komunikasi nonverbal dan menjadi indikasi penyelesaian konflik, pengikat tali persaudaraan, tanda penghormatan, penerimaan dan rasa terimakasih. Filosofinya adalah hidung menggambarkan kehidupan, mata menggambarkan kejujuran dan ketulusan, tangan menggambarkan relasi harmonis dirajut kembali atau dipertahankan. Tujuan penulisan untuk mengkaji tradisi hengeÃ¢â‚¬â„¢dho dari perspektif psikologis. Manfaatnya sebagaiÃ‚Â upaya mengembangkan dan mempertahankan nilai-nilai persaudaraan yang terkandung dalam budaya lokal. Teori interpersonal, Sullivan mengatakan manusia mengembangkan kepribadian dalam konteks sosial. Perkembangan manusia yang sehatÃ‚Â bergantung pada kemampuannya untuk mencapai keintiman denganÃ‚Â orang lain. Bagi masyarakat Sabu, cara menjalin hubungan dengan orang lain yaitu dengan hengeÃ¢â‚¬â„¢dho. Aspek psikologis dalam tradisi hengeÃ¢â‚¬â„¢dho adalah forgiveness, affection, intimacy, dan belief.Savu is an island located in East Nusa Tenggara Province. The Savu community has a unique tradition of establishing and maintaining relationships between people regardless of gender, ethnicity, race, religion, status, age and social strata called henge'dho (kissed nose). Henge'dho is a form of nonverbal communication and is an indication of conflict resolution, ties of kinship, signs of respect, acceptance and gratitude. The philosophy is the nose depicts life, the eyes depict honesty and sincerity, the hands describe harmonious relations knitted back or maintained. The purpose of writing is to examine the henge'dho tradition from a psychological perspective based on the results of a literature review. The benefits are as an effort to develop and maintain the values of brotherhood contained in local culture. In this literature review, the authors use articles sourced from electronic data bases in the form of unpublished electronic newspapers, theses and interview. Data that has been obtained, reviewed, compared, systematically arranged and discussed. Sullivan's interpersonal theory states that humans develop personalities in the context of social development. Healthy human development depends on its ability to achieve intimacy with others. For Savu people, the way to build relationships with others is by henge'dho. From several sources it is found that there are four psychological aspects in the tradition of henge'dho, namely forgiveness as a form of releasing anger or the desire to take revenge and revenge against those who have hurt us, affection states a form of affection for others, and belief is based on a tribal religious belief system that exists on the island of Sabu, namely Jingitiu..